ANALYSIS OF MODIFICATIONS OF SELF-ORGANIZING KOHONEN MAPS BY THE CRITERIA OF REGULARITY AND ACCURACY OF APPROXIMATION - Kiprich, T. V.; Dubrovin, V. I. (Radio Electronics, Computer Science, Control, 2024)
The interference problem of accuracy and regularity of the net among various self-organizing Kohonen’s map modifications is considered. The comparative analysis of these modifications over the cycles amount of training map, errors of quantization and topographical neurons ordering is given.